Knowing and Understanding the Tuberculosis (Tb) Disease of the Lung (Literature Review) - Arsyad, M. Hatadi; Syafina, Ikhfana; Hapsah, Hapsah; Hervina, Hervina (International Journal of Natural Science Studies and Development (IJOSS), 2024)
Tuberculosis is a highly prevalent disease among individuals. The bacteria may enter the human body with inhaled air, after which they will be taken into the lungs, and then might disseminate from the lungs into the other parts of the body via the circulatory system, lymphatic system, respiratory tract-bronchi, or by direct passage to other areas. The most affected organs with tuberculosis are the lungs, but it may also affect other organs, including the meninges, bones, superficial glands, and other organs. They include: India, 26%; Indonesia, 8.5%; China, 8.4%; the Philippines, 6%; Pakistan, 5.7%; Nigeria, 4.4%; Bangladesh, 3.6%; and South Africa, 3.6%. These eight countries account for two-thirds of the global cases put together. 8.2% of tuberculosis cases are co-infected with HIV. Targeted by the national tuberculosis control program is the elimination of tuberculosis by 2035 and attainment of a tuberculosis-free status by 2050. Methods: This study is based on a review of general clinical practice guidelines, research publications, websites, and textbooks on pulmonary tuberculosis. Findings and Analysis: There are various research writings about the clinical presentations of the condition, confirmatory investigations for Mycobacterium tuberculosis, the epidemiology of the patients, and risk conditions that predispose a patient to getting infected by the bacteria. Therapeutic interventions and pharmacological adverse effects. Conclusion Pulmonary tuberculosis is a communicable disease, and Indonesia still has a population that carries this infection. Thus, prevention of the disease should be done by every single individual in society by understanding and knowing the character of the disease.